Viridins, Bacteriocins of Alpha-Hemolytic Streptococci: Isolation, Characterization, and Partial Purification - Dajani, Adnan S. (1976)
Bacteriocin-like activities were detected in 78% of 120 alpha-hemolytic streptococcal isolates. Inhibitory substances from three such isolates (one Streptococcus sanguis strain and two S. mitis strains) were investigated further and termed viridins (A, B, and C). The viridins were unique among bacteriocins of gram-positive bacteria in that they inhibited many gram-negative bacteria in addition to inhibition of a variety of gram-positive organisms. Viridins were obtained in a cell-free state only after mechanical disruption of bacteriocinogenic cells but could not be isolated from supernatant fluids of cultures of such bacteria or from freeze-thaw liquor of agar on which the bacteria had been grown. Viridin B could be partially purified by ammonium sulfate precipitation and by gel filtration on a Sephadex G-100 column. This bacteriocin had some unusual properties including heat lability, a narrow pH range of activity, and lack of adsorptive capacity to susceptible bacteria. Although viridin B was bactericidal to a Neisseria sicca strain, it was only bacteriostatic against a coagulase-negative staphylococcus.